2020
DOI: 10.3727/096504020x15925659763817
|View full text |Cite|
|
Sign up to set email alerts
|

Programmed Death Ligand-1 (PD-L1) Regulated by NRF-2/MicroRNA-1 Regulatory Axis Enhances Drug Resistance and Promotes Tumorigenic Properties in Sorafenib-Resistant Hepatoma Cells

Abstract: Sorafenib, a multi-tyrosine kinase inhibitor, is a standard treatment for advancedhepatocellular carcinoma (HCC), but the clinical response to sorafenib is seriouslylimited by drug-resistance. Programmed death ligand-1 (PD-L1) is one of the mostimportant inhibitory molecules involved in tumor immune evasion. Recently, it has beenreported that PD-L1 could play crucial roles in drug-resistance of many kinds ofcancers. However, the expression, function and regulation of PD-L1 in sorafenibresistanthepatoma cells r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Yao et al (42) reported that PD-L1 expression by macrophages was positively regulated by the PI3K/Akt signaling pathway, in support of the current results. Another study previously reported that PD-L1 expression by liver cancer cells was regulated by the Nrf2 pathway (43), and a previous report by the authors previously revealed that VEGF secreted by TAMs may activate the Nrf2 pathway in liver cancer cells (18). Therefore, VEGF inhibition can suppress the VEGF autocrine loop in macrophages and reduce PD-L1 expression in cancer cells through the inactivation of the AKT/mTOR pathway in TAMs, possibly due to the suppression of the Nrf2 pathway in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Yao et al (42) reported that PD-L1 expression by macrophages was positively regulated by the PI3K/Akt signaling pathway, in support of the current results. Another study previously reported that PD-L1 expression by liver cancer cells was regulated by the Nrf2 pathway (43), and a previous report by the authors previously revealed that VEGF secreted by TAMs may activate the Nrf2 pathway in liver cancer cells (18). Therefore, VEGF inhibition can suppress the VEGF autocrine loop in macrophages and reduce PD-L1 expression in cancer cells through the inactivation of the AKT/mTOR pathway in TAMs, possibly due to the suppression of the Nrf2 pathway in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of PD-L1 has been proven to promote immune evasion and tumor growth in HCC by suppressing tumor-infiltrating lymphocytes, and the mechanism mainly involves reduction of cytotoxic CD8 + T cells and expression of cytokines ( 20 , 30 ). Aberrant upregulation of PD-L1 was observed in sorafenib-resistant HCC cells and overexpression of PD-L1 played an essential role in developing and maintaining resistance to sorafenib which contributed to persistent aggressiveness of HCC cells ( 31 ). PD-L1 facilitated EMT and aggressive properties of sorafenib-resistant cells by activating PI3K/Akt pathway which was modulated by expression of Sterol regulatory element-binding protein 1 (SREBP-1) ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…PD-L1 facilitated EMT and aggressive properties of sorafenib-resistant cells by activating PI3K/Akt pathway which was modulated by expression of Sterol regulatory element-binding protein 1 (SREBP-1) ( 21 ). Reversal of EMT was observed after knockdown of PD-L1 and sensitivity of HCC cells to sorafenib was significantly improved ( 31 , 32 ). More importantly, unlike TNF-α ( 26 ), the aforementioned predictor for RFS which was not influenced by sorafenib treatment, PD-L1 expression was significantly upregulated upon exposure to sorafenib and in sorafenib-resistant HCC ( 20 , 31 , 33 ), and also in relapsed HCC ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations